Olive harvesting in Syria [printed version also available in Arabic] - Abdine M.; Jbara G.; Bourghoul A.; Cardone G.L.; Dubla E.; Dragotta A.; Contento F.; Famiani F. (Syrian national strategic plan for olive oil quality : final report, 2007)
In the period 2005-2006, demonstrative trials to evaluate the efffectiveness of hand-held machines to harvest the fruits of some of the main olive Syrian cultivars were carried out. At the present time, almost all the olives produced in Syria are harvested by hand from the trees because manpower cost is relatively low but the worker productivity too : 6-20 kg/h/worker. In November 2005, two hand-held machines, a pneumatic comb and an electric whipper were compared with one another and with manual harvesting, on adult trees, of the two main Syrian olive cultivars: Sorani (Idleb area) and Zaity (Aleppo area). The harvesting yield was 96-97 percent with manual harvesting and ranged from 92 to 95 percent with the machines. With respect to manual harvesting, working productivity increased about 3.5-4 times with the cultivar Zaity and 4.5-5 times with the cultivar Sorani using the electric whipper and pneumatic comb. The results were good and promising, considering that the two regions and cultivars taken into account represent about 60 per cent of the total surface area cultivated with olives in Syria. In November 2006, these interesting results were substantially confirmed in demonstrative trials carried out with pneumatic combs, in Homs, Salamieh and Hama areas, on the cultivars Doebli and Kaissy. Suggestions are given in order to improve the impact of olive harvesting on the quality of the product and on the economical revenue of olive cultivation in Syria.